Childhood bruxism - Trisha Das Sarma; Abhishek Mandal; Shabnam Zahir; Gautam Kumar Kundu (Wolters Kluwer Medknow Publications, 2019)
Bruxism is diurnal or nocturnal parafunctional habits which includes repetitive jaw-muscle activities, clenching or grinding of the teeth and/or bringing forward the mandible. Psychological components, genetic components, peripheral and patho-physiological components are the main Etiology of bruxism. Treatment options include occlusal rehabilitation, behavioural and pharmacological therapy. We perform a scientific paper search by using ebscohost, pubmed, and Google search engines. The searched item 'Bruxism' showed total 1125 papers, among which 250 were review papers. Most of them were published between 1990 to 2017 and some of them before 1990. Through this review an overview about childhood bruxism and its various treatment options and outcomes will be provided.